2005
DOI: 10.1191/0969733005ne817oa
|View full text |Cite
|
Sign up to set email alerts
|

Deferred Decision Making: patients’ reliance on family and physicians for cpr decisions in critical care

Abstract: The aim of this study was to investigate factors associated with seriously ill patients' preferences for their family and physicians making resuscitation decisions on their behalf. Using SUPPORT II data, the study revealed that, among 362 seriously ill patients who were experiencing pain, 277 (77%) answered that they would want their family and physicians to make resuscitation decisions for them instead of their own wishes being followed if they were to lose decision-making capacity. Even after controlling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…41 One prior study found that patients who opted for cardiopulmonary resuscitation in end-of-life discussions were twice as likely to rely on family and physicians to make resuscitation decisions. 42 However, in our exploratory analysis, we found that none of the participants with low DCPs wanted family or friends to take over this role. Without designation of a surrogate decision maker, conflicts may arise when deciding how to proceed according to the patient's best interest.…”
Section: Discussionmentioning
confidence: 76%
“…41 One prior study found that patients who opted for cardiopulmonary resuscitation in end-of-life discussions were twice as likely to rely on family and physicians to make resuscitation decisions. 42 However, in our exploratory analysis, we found that none of the participants with low DCPs wanted family or friends to take over this role. Without designation of a surrogate decision maker, conflicts may arise when deciding how to proceed according to the patient's best interest.…”
Section: Discussionmentioning
confidence: 76%
“…33 These assumptions however are not consistent with the results of empirical studies that show that even ''mainstream'' Western patients prefer relationship-based autonomy rather than strictly interpreted individual autonomy. [34][35][36][37][38][39] What is therefore needed is a patient-centered approach to ACP that can accommodate the different perspectives in decision-making style and the unit of care. It is important during the ACP process to clarify the basic unit through which important decisions can be made and care can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that most inpatients who are older or have serious illnesses would not want their prior stated resuscitation preferences automatically followed if they were to lose decision-making capacity. Most patients in both groups would prefer their family and physician to make resuscitation decisions for them 19 20. The responsibility for making these decisions can be hard on the surrogate, although there are no data on what patients think of this pressure 21…”
Section: Introductionmentioning
confidence: 99%